PSIKOLOGI DALAM PERSPEKTIF AL-FARABI DAN SIGMUND FREUD - Chasanatin, Haiatin (JURNAL TARBAWIYAH, 2014)
The rapid development of contemporary psychology has absent-minded some of Islamic thinkers. The results of Western thought that not infrequently lead to bias, often massively adopted without a careful analysis. Referring to movement science Islamisasi initiated by Ismail Raji al-Faruqi, this study aims to conduct a comparison between the concepts of psychology in the view of Al - Farabi and Sigmund Freud. Both of them are central figure in the development of contemporary psychology and the psychology of Islam.In this paper will be presented on the concept of psychology in perspective Al - Farabi and Sigmund Freud. From the results of this study concluded that there are similarities and differences between the concepts of psychology according to Al - Farabi and Sigmund Freud. The equation is found in the discussion of aspects of human jasmaniyah while striking difference was found in ruhaniyah aspects. The second aspect is not at all touched by the concept of psychoanalysis Freud. The difference has impact to different patterns of personality offered by the two men.Â Keywords: psychology, Al - Farabi and Sigmund Freud, and psychology of Islam